Meta-Analysis: The Effects of Workload and Social Support on Burnout in Health Workers - Hanifah; Sumardiyono; Murti, Bhisma (Journal of Health Policy and Management, 2023)
Background: Burnout is a psychological syndrome of exhaustion, cynicism and ineffectiveness at work. Some factors causing burnout are workload and family support. The existence of a high workload can increase the incidence of burnout and high social support can prevent burnout in health workers. This study aims to estimate the effect of workload and social support on burnout in health workers. Subjects and Method: A systematic review and meta-analysis was carried out using the PRISMA guidelines and the PICO model covering Population = health workers; Intervention = high workload and high social support; Comparison = low workload and low social support; Outcome = burnout. Articles were collected from databases such as PubMed, Science Direct, and Google Schoolar. The keywords used in the database search were workload AND "social support" AND burnout OR fatigue AND "health workers" AND "cross sectional".A total of 12 articles met the inclusion criteria for the meta-analysis and were assessed using RevMan 5.3. Results: Meta-analysis from France, Afghanistan, Canada, Uganda, Ghana, Ethiopia, Malawi, Brazil, Malaysia and China showed that high workloads can increase burnout in health workers (aOR= 2.37; 95% CI= 1.10 to 5.10; p = 0.003), high social support can reduce the risk of burnout in health workers (aOR= 0.54; 95% CI= 0.42 to 0.71; p= 0.001), and these results were statistically significant. Conclusion: High workload can increase burnout among health workers and high social support can reduce the risk of burnout in health workers. Keywords: workload, social support, burnout, health workers Correspondence: Hanifah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: hanifah1611@gmail.com. Mobile: 081226829788.